PERAN DESA ADAT BALI DALAM MELANCARKAN KEBIJAKAN PENANGGULANGAN PANDEMI COVID-19 - I Made Chandra Mandira; Cokorda Krisna Yudha (Universitas Halu Oleo, 2021)
Traditional villages have become the spearhead of community activities, especially in Bali. Regional Regulation (Perda) No.4 of 2019 concerning Traditional Villages is a breath of fresh air for indigenous people in Bali because it has legal legitimacy and recognition. Traditional villages played an important role during the covid-19 pandemic in Bali because they were at the forefront of protecting their territories, from securing the area to distributing social assistance. This study aims to analyze the strategies carried out by the government through customary villages to launch policies during the Covid-19 pandemic. The method used in this research is a literature study, where the data obtained will be compiled, analyzed, and concluded which will lead to conclusions about the literature study of Balinese traditional villages as a strategy in launching policies during the pandemic. This study found that customary villages are a team that embodies effectiveness in efforts to tackle Covid-19 starting from the context, composition, and process in it to solidarity with social groups derived from local wisdom values. The welfare of members of customary villages, especially those assigned to the task force for handling Covid-19, must be considered and the regional government should not use a generic strategy to archive low costs and broad differentiation in implementing policies